Kinerja Lembaga Penyiaran Publik Radio Republik Indonesia (Studi Tentang Kinerja Pegawai di Lembaga Penyiaran Publik RRI Manado) - Makawimbang, Halmintje; Rumapea, Patar; Ruru, Joorie (JURNAL ADMINISTRASI PUBLIK, 2015)
Abstract : This research aims to analyze the performance of a Public Broadcasting Institution theradio Indonesia Republic in Manado. Public Broadcasting Institution the radio Indonesia Republic inManado as a government bureaucracy is the one work unit in North Sulawesi. Public BroadcastingInstitution the radio Indonesia Republic in Manado is institutions that convey information as well as news –actual and reliable news as well as provide entertainment to the community particularly the city of Manado.To carry out its work, Public Broadcasting has a function a. Deliver/broadcast news and Information toactual and reliable, providing wholesome Entertainment to the community. The central problem in the studybased on the pre survey, for example, the protection of the rights of women workers, safety (safety securitywork) and also a guarantee against social workers. Qualifying employees in particular HR limitations ofEchelon IV also become constraints in the implementation of tasks and jobs. In addition still lack of trainingtrainingis to support the technical skill employees create a work to be hampered due to the lack of technicalknowledge of employees in carrying out his job. Therefore, in a situation like this, the head of Department orhead of the need to conduct performance assessment to review the extent to which employee performance andevaluate the effectiveness of the deficiencies contained therein so that action can be taken as soon as possibleto resolve the issue.In this study the author uses a quantitative approach. quantitative data processing-data that isobtained from the location of the research with data collection techniques: study library and study field, asfor Informants in this study was the assessment of officials is tops on Public Broadcasters, among them headof the radio Indonesia Republic in Manado Station, the head of the field and the head section.The results of this research are generally speaking the performance of employees in the PublicBroadcasting Institution the radio Indonesia Republic in Manado can be said to have good, based on thefinal value of each employee's performance with Employees Working Objectives values accumulate (SKP)and overall work so that Behavior can be inferred to be on the level of "good". But there are some drawbackson a number of aspects that need to be addressed. There are also some drawbacks in the system assessmentsbased Government Regulations No 46-year 2011 as in some aspects of the assessment that does not have aclear criteria in measuring these aspects in the assessment being thus causing less accurate, as well as theassessment is very subjective because it is only rated by his superiors only and does not involve otherelements associated with it. Further, the ratings only measure the performance on an individual basis andnot on the team's performance while at the moment the work more charged on teamwork, not merely on theindividual.Referring to the discussion and the conclusions above, the suggested performance in order toimprove Employee Public Broadcasting Institution the radio Indonesia Republic in Manado then needs to bein the presence of Required training To suggest as well as employee development programs so that theperformance achieved by the Public Broadcasting Institution the radio Indonesia Republic in Manado can beincreased again in all its aspects. There should be a review of employee performance appraisal system basedGovernment Regulations No 46-year 2011 About assessment performance achievements of employeesbecause there were still some shortcomings in it. then to measure employee performance, We recommendthat you use team-based performance measurement because at the moment most of the work that is given toemployees is work done in teams, so hopefully the performance will be better achieved.Keywords: Performance, Public Broadcasting Institution Radio Indonesia Republic